The seismography of crashes in financial markets - Araújo, Tanya (2010)
This paper investigates the dynamics of stocks in the S&P500 for the last 33 years, considering the population of all companies present in the index for the whole period. Using a stochastic geometry tech¬nique and defining a robust index of the dynamics of the market struc¬ture, which is able to provide information about the intensity of the crises, the paper proposes a seismographic classification of the crashes that occurred during the period. The index is used in order to inves¬tigate and to classify the impact of the twelve crashes between July 1973 and March 2006 and to discuss the available evidence of change of structure after the fin de sicle.